Quantitative assessment of salivary oral bacteria according to the severity of dental caries in childhood - Colombo, Natália H. [UNESP]; Kreling, Paula F. [UNESP]; Ribas, Laís F.F. [UNESP]; Pereira, Jesse A. [UNESP]; Kressirer, Christine A.; Klein, Marlise I. [UNESP]; Tanner, Anne C.R.; Duque, Cristiane [UNESP] (Elsevier, 2017)
This study aimed to assess differences in selected oral bacteria in children according to the severity of dental caries. One hundred and thirty-six children, 36–60 months old were divided into three groups according to caries status: caries-free (CF) (n = 47), early childhood caries (ECC) (n = 40) and severe-early childhood caries (S-ECC) (n = 49). Saliva was collected for detection and quantification of selected oral streptococci, Actinomyces naeslundii, Lactobacillus spp., Bifidobacterium spp., and Scardovia wiggsiae by quantitative-polymerase chain reaction. The results showed that the detection and quantitative levels of S. mutans, S. sobrinus, Bifidobacterium spp. and S. wiggsiae were significantly higher in S-ECC children compared to CF and ECC children, while for S. salivarius were significantly higher in CF compared to ECC and S-ECC children. There was no statistical difference among the clinical groups for S. mitis, S. oralis, A. naeslundii and Lactobacillus spp. levels and detection. S-ECC children had a lower monthly family income, started tooth brushing later and were breastfeed for a longer duration compared to CF children. S. mutans levels were positively correlated with S. wiggsiae and Bifidobacterium spp. levels, lower mother's education and child bottle-feeding before sleeping and negatively correlated with S. salivarius. It was concluded that in addition to S. mutans, other bacterial species, including bifidobacteria, Scardovia wiggsiae and S. sobrinus, are associated with severity of early childhood caries, although their role in the progress of dental caries remains unclear.
Keywords: Early childhood caries; Oral bacteria; Quantitative polymerase chain reaction